2001
DOI: 10.1054/bjoc.2000.1628
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma is genetically distinct from clear cell sarcoma of tendons and aponeurosis (malignant melanoma of soft parts)

Abstract: Summary Clear cell sarcoma of tendons and aponeuroses (malignant melanoma of soft parts) and conventional malignant melanoma may demonstrate significant morphologic overlap at the light microscopic and ultrastructural level. Consequently, the clinically relevant distinction between primary clear cell sarcoma and metastatic melanoma in the absence of a known primary cutaneous, mucosal or ocular tumour may occasionally cause diagnostic problems. A balanced translocation, t(12;22)(q13;q13), which can be detected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
80
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 26 publications
1
80
0
4
Order By: Relevance
“…EWS/ATF1 transcript types 1, 2 and 3 had been found in 9, 3 and 1 tumors, respectively. 10,11,[13][14][15][16][17][18][19] In the present study, 3 cases showed multiple transcripts as the result of alternative splicing. The most common fusion transcript was type 1 (EWS exon 8 fused with ATF1 exon 4), found in 8 patients, followed by type 2 (EWS exon 7 fused with ATF1 exon 5), found in 4 patients, though only in 1 case as the sole chimeric transcript (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…EWS/ATF1 transcript types 1, 2 and 3 had been found in 9, 3 and 1 tumors, respectively. 10,11,[13][14][15][16][17][18][19] In the present study, 3 cases showed multiple transcripts as the result of alternative splicing. The most common fusion transcript was type 1 (EWS exon 8 fused with ATF1 exon 4), found in 8 patients, followed by type 2 (EWS exon 7 fused with ATF1 exon 5), found in 4 patients, though only in 1 case as the sole chimeric transcript (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…13 To date, only 13 cases of CCS have been analyzed for fusion genes at the transcription level and there is no information about the breakpoints at the genomic level. 10,11,[13][14][15][16][17][18][19] In the present study, we describe the molecular genetic characteristics of CCS from 10 patients.…”
mentioning
confidence: 99%
“…6 At the molecular level, alterations of the p16INK4a/ p14ARF pathway are present in both clear cell sarcoma and malignant melanoma. 25 Although originally reported to be genetically distinct from malignant melanoma, 16 recent genomic profiling data suggest that clear cell sarcoma is a subtype of melanoma. 26 However, in contradistinction to malignant melanoma, clear cell sarcoma harbors EWS gene rearrangements in up to 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, in contradistinction to malignant melanoma, clear cell sarcoma harbors EWS gene rearrangements in up to 90% of cases. [11][12][13][14][15][16][17][18][19]27 Thus, translocations involving EWS are diagnostically useful for distinguishing clear cell sarcoma from its most important mimic malignant melanoma. 19 Although not a hypothesis tested in this study, clear cell sarcoma could conceivably be distinguished from benign melanocytic proliferations that mimic malignant melanoma, such as cellular blue nevi, deep penetrating nevi, and proliferative nodules arising within congenital nevi, as these lesions have not been reported to contain EWS gene rearrangements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation